2016
DOI: 10.1038/mto.2016.1
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic vesicular stomatitis virus expressing interferon-σ has enhanced therapeutic activity

Abstract: Oncolytic viruses are known to stimulate the antitumor immune response by specifically replicating in tumor cells. This is believed to be an important aspect of the durable responses observed in some patients and the field is rapidly moving toward immunotherapy. As a further means to engage the immune system, we engineered a virus, vesicular stomatitis virus (VSV), to encode the proinflammatory cytokine interferon-γ. We used the 4T1 mammary adenocarcinoma as well as other murine tumor models to characterize im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 43 publications
1
55
0
Order By: Relevance
“…In addition, some OVs appear to induce immunogenic cell death rather than autophagy (20,21). Oncolytic rhabdoviruses like Maraba and vesicular stomatitis virus (VSV) have been shown to enhance natural killer cell-mediated killing of tumor cells (22), dendritic cell maturation, up-regulation of antigen presentation by tumor cells (23), and the production of proinflammatory cytokines and chemokines (23)(24)(25)(26). Here, we demonstrate that the production of several chemokines and cytokines by tumor cells relies on both RIG-I and MYD88 signaling, depending on the tumor model.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, some OVs appear to induce immunogenic cell death rather than autophagy (20,21). Oncolytic rhabdoviruses like Maraba and vesicular stomatitis virus (VSV) have been shown to enhance natural killer cell-mediated killing of tumor cells (22), dendritic cell maturation, up-regulation of antigen presentation by tumor cells (23), and the production of proinflammatory cytokines and chemokines (23)(24)(25)(26). Here, we demonstrate that the production of several chemokines and cytokines by tumor cells relies on both RIG-I and MYD88 signaling, depending on the tumor model.…”
Section: Discussionmentioning
confidence: 80%
“…Overall, VSVD51-IFNg reduced the number and size of lung tumours in the 4T1 immunocompetent mouse model and demonstrated better efficacy compared to the parental virus. This improved efficacy was lost in immunocompromised animals, suggesting that the mechanism is T-cell-dependent [116].…”
Section: Inducing Tumour-specific Immunitymentioning
confidence: 99%
“…Non-small cell lung cancer [128], [129], Improved survival mouse model [61] Not reported VV [128] Mesothelioma [61], Pancreatic adenocarcinoma [59] VSV [129] NDV [59] IFN-γ NDV [55] Melanoma [55], Mammary and colon carcinoma [62] Increased cytokine expression and improved DC maturation [62] Not Reported VSV [62] Increased T cell infiltration [55] Others: IL-18 [30], [108], IL-17 [130], TNF [55], MIP1a [131], FLT3L [131] NDV [55] Improved T cell responses Not reported VSV [130] AdV [108] HSV [30] Chemokines: CCL5 [65], CCL2 [67], CCL19 [132], CXCL11 [64], [133] VV [65,66,122,123] Colon carcinoma Improved DC maturation [65] Not reported HSV [67] Improved infiltration T helper cells and CTLs [64], [65], [132], [133] Induces a Th2 response, but reverts to a Th1 response in combination with DC vaccination [65] Co-stimulatory ligands B7.1/CD80 HSV [84] Neuroblastoma [84], Melanoma (patients) a [86] Immunity against rechallenge with tumor cells [84] Low g...…”
Section: Il-15mentioning
confidence: 99%
“…IFN-γ upregulates MHC I expression in tumor cells and promotes Th1 skewing via an autocrine loop [23]. A recent study describing VSV expressing IFN-γ suggested that this virus induces a stronger immune response by increasing MHC I antigen presentation on tumor cells, enhancing DC maturation and attracting T cells to the tumor site by inducing CCL2 expression in mice [62]. The authors did not observe any difference in viral replication, even though IFN-γ is also known for its antiviral activity.…”
Section: Type I and Ii Interferonsmentioning
confidence: 99%